(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Modern cetaceans are considered the best anatomical and ecological analogue for many Mesozoic secondary aquatic reptiles. Such similarities extend also after the death of these phylogenetically distant amniotes, when the sinking and decomposition of large carcasses in marine environments (deadfalls) follow common biostratinomic processes. Most taphonomic studies on Mesozoic deadfalls have been limited to shallow-water settings, often neglecting deeper waters. Here we provide a detailed taphonomic survey of ichthyosaurs, pliosaurs and metriorhynchoids from the pelagic Middle-Upper Jurassic Rosso Ammonitico Veronese (RAV) of northeastern Italy. Our taphonomic revision of the RAV tetrapod record highlights a common poor state of preservation of the bones, often associated with abundant macrofossils, consistent with a prolonged exposure of carcasses on a well-oxygenated seafloor. For the first time we confirm the role of nautiloids as active mobile scavengers by means of tens of beak elements found closely associated with, or even piercing, the bones. Hexanchiform shark teeth are also found associated with the carcasses, supporting a distinctive deep-water mobile scavenging community. Echinoids, sponges and other bioeroders are identified as representative of the enrichment-opportunist stage, and a high concentration of belemnites is believed to be indicative of mass-spawning deaths in the surroundings of the carcasses. Abundant crinoids are recognized as part of the reef stage by colonization of the eroded bones. While some of our data deviate from previous Mesozoic reptile-falls from shallow-waters, they are consistent with findings at Recent whale-falls in bathyal zones, and overall represent a precious window into the complex ecology of Jurassic open seas.